ANALYSIS OF THE MEANING SHIFT OF THE LOANWORD TECHNOLOGY IN INDONESIAN USING THE WORD EMBEDDING TECHNIQUE - Fathoni, Ahmad; Mawe, Hannatul; Alfan Habib, Muhammad; Fitriani, Fitriani (PT. GWEX NET PUBLISHER, 2025)
The development of information technology has encouraged the widespread adoption of technology-related loanwords in the Indonesian language, particularly in digital communication. The intensive use of these loanwords across diverse contexts has led to semantic shifts in their meanings. This study aims to analyze semantic shifts in technology-related loanwords in Indonesian by employing word embedding techniques as a computational linguistic approach. The research adopts a quantitative method based on the analysis of Indonesian digital text corpora representing language use across different time periods. The data are analyzed through text preprocessing, word embedding modeling, and the measurement of semantic relationship changes using cosine similarity and nearest-neighbor analysis. The results indicate that several technology-related loanwords have undergone significant semantic shifts, including meaning expansion, changes in semantic associations, and shifts in usage functions in line with technological developments and digital culture. These findings demonstrate that word embedding techniques are effective for empirically detecting semantic shifts in Indonesian. This study is expected to contribute methodologically to Indonesian semantic studies and to enrich corpus-based computational linguistics research.